Trained Immunity and HIV Infection - Sviridov, Dmitri; Miller, Yury I.; Bukrinsky, Michael I. (Frontiers in Immunology, 2022)
Findings that certain infections induce immunity not only against the causing agent, but also against an unrelated pathogen have intrigued investigators for many years. Recently, underlying mechanisms of this phenomenon have started to come to light. It was found that the key cells responsible for heterologous protection are innate immune cells such as natural killer cells (NKs), dendritic cells, and monocytes/macrophages. These cells are ‘primed’ by initial infection, allowing them to provide enhanced response to subsequent infection by the same or unrelated agent. This phenomenon of innate immune memory was termed ‘trained immunity’. The proposed mechanism for trained immunity involves activation by the first stimulus of metabolic pathways that lead to epigenetic changes, which maintain the cell in a “trained” state, allowing enhanced responses to a subsequent stimulus. Innate immune memory can lead either to enhanced responses or to suppression of subsequent responses (‘tolerance’), depending on the strength and length of the initial stimulation of the immune cells. In the context of HIV infection, innate memory induced by infection is not well understood. In this Hypothesis and Theory article, we discuss evidence for HIV-induced trained immunity in human monocytes, its possible mechanisms, and implications for HIV-associated co-morbidities.